2016
DOI: 10.7888/juoeh.38.17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Diagnostic Yield of Endobronchial Ultrasonography with a Guide Sheath for Peripheral Lung Cancer

Abstract: Endobronchial ultrasonography with a guide sheath (EBUS-GS) has recently been used for improved diagnostic yields for peripheral pulmonary lesions. This study retrospectively evaluated the factors related to the diagnostic yield of EBUS-GS for peripheral lung cancer. The medical records of 76 patients who had been diagnosed with lung cancer and had undergone bronchoscopy with EBUS-GS in our hospital between August 2014 and September 2015 were reviewed. The total diagnostic ratio of peripheral lung cancer was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Our application of the QUADAS‐2 tool showed that these studies therefore had an undetermined risk of bias in the flow and timing component. Table S1 (Supplementary Information) lists all included studies and their performance based on QUADAS‐2 tool …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our application of the QUADAS‐2 tool showed that these studies therefore had an undetermined risk of bias in the flow and timing component. Table S1 (Supplementary Information) lists all included studies and their performance based on QUADAS‐2 tool …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows a Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) flow diagram summarizing the above‐mentioned data. Of the 57 studies included in the meta‐analysis, 2 were in Chinese and 1 was in Japanese . Rest of the studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the diagnostic yield of EBUS-GS can improve with an increase in the number of procedures performed, particularly among beginners (7). In summary, training is considered one of the most important factors contributing to an improved diagnostic yield of EBUS-GS for PPLs (8). However, the most suitable model for providing hands-on training in EBUS-GS remains to be elucidated.…”
Section: Original Articlementioning
confidence: 99%
“…In addition, a Japanese study has shown that bronchoscopy training is an important factor for improving the diagnostic yield of EBUS-GS in PLC. [ 40 ]…”
Section: Improvement Of the Diagnostic Yield Of Endobronchial Ultrasomentioning
confidence: 99%